(3cfR GdYQaGf aj Yde GdMSGHs - (3GdMSf Hf MQH GdMjhHjs
(3ChdgG (B:s
(3bGd GdMSf Hf MQH GdMHhHi Cf CLd GdYdhe GdTQYjI HYO eYQaI Gddg JYGdi hSGFQ eG jaJQV YdjfG ef JUOjb GdfHi s
(3BNQgG (B:s
(3GdebGdI GdSGOSI Jchf eVQhH C H ai H M` eSGhjkG deQHY H g` hPdc eG GQOfG Cf fHjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs